(untitled) (Fiep Bulletin - online, 2014)
Currently there are many professionals serving that still have the academic turned to a predominance of the trend Tecnicista, and these also are present in the training of future professionals of the courses for Physical Education. Thus, the present work with teachers to identify objectives of the courses of Degree in Physical Education of the West of Parana, if there is any influence of motor skills in the teaching-learning process of their discipline in the training of these scholars. The search has descriptive nature, with the population of teachers Institutions of Higher Education of the courses of Degree in Physical Education in the Region west of Parana. The results pointed found that the teachers believe that academic owners of motor skills have greater possibilities of learning in their training and may also become better professionals, pointing still a vision within the trend tecnicista, showing traces of their training these teachers that was characterized as technique. Thus, this training has a character in the training of new professionals for these teachers. Thus we believe that the motor skills to contribute to the formation of these scholars with form and content with not predominant factor to their training, we realize that some of these teachers still have a wrong vision of the future training of these professionals, but this learning is incorporated individually it can not and should not be the factor fundante the teaching-learning process in the academic.